2014
DOI: 10.4236/msa.2014.56043
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Surface Morphology and Structural Characterization of Palm Fiber Reinforced Acrylonitrile Butadiene Styrene (PF-ABS) Composites

Abstract: With the aid of Injection Moulding Machine (IMM) Palm fiber reinforced Acrylonitrile Butadiene Styrene (ABS) composites (PF-ABS) were prepared. Three sets of samples were prepared for three different wt% (5%, 10% and 20%) of fiber contents. Scanning Electron Microscopy (SEM), X-ray diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FTIR) experiments were performed to study the surface morphology, microstructure (if it crystalline or noncrystalline) and new bond formation after preparation of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Figure a depicts the variation in XRD patterns between base components such as ABS, MA‐ g ‐ABS, and EVA at ambient temperature. It is observed that pristine ABS showed a broad peak between 15° and 30°; 2 θ indicates its amorphous nature . Comparatively, an intense peak was observed for MA‐ g ‐ABS at 1° lower 2 θ value than the native ABS.…”
Section: Resultsmentioning
confidence: 91%
“…Figure a depicts the variation in XRD patterns between base components such as ABS, MA‐ g ‐ABS, and EVA at ambient temperature. It is observed that pristine ABS showed a broad peak between 15° and 30°; 2 θ indicates its amorphous nature . Comparatively, an intense peak was observed for MA‐ g ‐ABS at 1° lower 2 θ value than the native ABS.…”
Section: Resultsmentioning
confidence: 91%
“…Figure presents the FTIR spectrum (frequency range of 400‐4000 cm −1 ) for barite, magnetite, pure ABS, ABS/barite composite, and ABS/magnetite composite. The major peaks of ABS polymer (698 cm −1 , 758 cm −1 , 910‐964 cm −1 , 1028 cm −1 , 1452‐1493 cm −1 , 2250 cm −1 , and 2918 cm −1 ) are due to the presence of C‐H out of plane, =C‐H out of plane bending, C‐H bending, C‐H in plane bending, asymmetry C‐H bending, C ≡ N stretching, and symmetric C‐H stretching bonds, respectively . A comparison of the spectra of barite, magnetite, ABS, ABS/barite composite, and ABS/magnetite composite showed that no new bonds were formed after compounding ABS with dense fillers.…”
Section: Resultsmentioning
confidence: 98%
“…The dense fillers had sharp peaks, which reveals the plane, =C-H out of plane bending, C-H bending, C-H in plane bending, asymmetry C-H bending, C ≡ N stretching, and symmetric C-H stretching bonds, respectively. [27] A comparison of the spectra of barite, magnetite, ABS, ABS/barite composite, and ABS/magnetite composite showed that no new bonds were formed after compounding ABS with dense fillers. Figure 3 shows the average transmission loss (sound insulation) values measured on pure ABS, ABS/barite composite and ABS/magnetite composites between 800 and 1600 Hz.…”
Section: Resultsmentioning
confidence: 99%
“…These polymers are of ease and give fantastic mechanical properties [22]. Then again, the ABS restrictions are: poor flame and chemical resistance, and low thermal stability [23].…”
Section: Introductionmentioning
confidence: 99%
“…Composites with different wt% of sawdust in ABS polymer (a): 0 wt%, (b): 5 wt%, (c): 10 wt%, (d): 15 wt%, and (e): 20 wt%.moulding machine. In these research works, three sets of composites samples were prepared with 5%, 10% and 20% fiber content to carry out these research[12] [23].…”
mentioning
confidence: 99%